Analisis Keandalan Fire Trucks Dalam Penanggulangan Bahaya Kebakaran di Industri Semen - Moch. Luqman Ashari; Nurul Afifah; Ainun Ulifiya Ulfa (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Abstract Cement Industry utilizes fire trucks as one of the main components in its fire fighting system within the accessible areas of the factory. As a result, research is needed to determine the efficiency and effectiveness of firefighting with the fire trucks in order to establish appropriate limitations. The research used is a type of qualitative research, with direct observation models and interviews with the fire team, which are descriptive in nature and aim to describe and present facts from an object of research in a systematic and detailed manner. This study used samples in the form of inspection lists of fire trucks or fire engines, fire & safety team structures, management policies, and data on coal fires. From the research results it was found that the reliability of fire trucks in fighting fires in the Cement Industry was not optimal. So, it is necessary to increase the specifications of fire trucks with the addition of a 33-meter ladder equipped with a water monitor camera and a ladder extending forward to evacuate trapped victims. Keyword fire, , fire, , Abstrak Industri Semen menggunakan fire trucks atau mobil pemadam kebakaran sebagai salah satu komponen utama dalam sistem penanggulangan kebakaran pada area pabrik yang dapat dijangkau. Akibatnya, diperlukan penelitian terkait efisiensi dan efektivitas penanggulangan kebakaran dengan fire trucks guna mendapatkan batasan yang lebih sesuai. Adapun penelitian yang digunakan adalah jenis penelitian kualitatif, dengan model observasi langsung dan wawancara bersama regu fire, yang bersifat deskriptif bertujuan untuk menggambarkan dan menyajikan fakta dari suatu objek penelitian secara sistematis dan detail. Penelitian ini menggunakan sampel berupa daftar inspeksi fire trucks atau mobil pemadam kebakaran, struktur regu fire & safety, kebijakan manajemen, dan data kebakaran batu bara. Dari hasil penelitian didapatkan bahwa keandalan fire trucks dalam penanggulangan kebakaran di Industri Semen belum optimal. Sehingga, perlunya peningkatan spesifikasi fire trucks dengan penambahan tangga 33 meter dilengkapi kamera water monitor serta jalur tangga menjulur ke depan untuk mengevakuasi korban yang terjebak. Kata Kunci kebakaran, mobil pemadam kebakaran, api, keselamatan, industri semen